Omoleon jeanneli, new record from Kenya and a redescription (Neuroptera: Myrmeleontidae) - Dobosz, Roland; Ábrahám, Levente (Zootaxa, 2014)
A poorly known species of antlions, Omoleon jeanneli Navás, 1936 is redescribed and illustrated with five photos and genitalia drawings. A key for African Dendroleontini is given. This is the first record of O. jeanneli from Kenya.